Effects of various jumping exercises on vertical force distribution and emg pattern in school children - Siti Musyrifah, Ismail (2008)
Purpose of the present study was to determine the effect of 9 weeks of training based on various jumping exercises on vertical force distribution and EMG pattern in school children. Forty school children (12 male and 28 female) aged between 13 to 17 years participated in this study. Subjects were divided evenly into 3 experimental groups: Group 1 (training based on jumps), Group 2 (training based on hops), Group 3 (training based on box drills) and a control group - Group 4. Intervention programme had been administered on the experimental groups for 9 weeks. During the 1st three weeks, the subjects were exercising once a week, followed by 3 weeks of exercising twice a week with last 3 weeks exercising thrice a week. No intervention programme was administered to the control group. Subjects were evaluated before, after 3 weeks (mid-test 1), 6 weeks (mid-test 2) and 9 weeks (post-test) in counter movement jump (CMJ), continuous jump with bent legs (CJb) and drop jump (DJ) with registration of jumps' characteristics and EMG. As a result, all intervention groups showed significant improvement in jump height and power within group between tests (p<0.001). By CMJ test, hop training brought highest improvements in jump height (27.9%) (p<0.001) and power (9.70%) (p<O.OOl), whereas box drills training improved force ( 15.5%) from pre-test values. Meanwhile by CJb test, jumps training brought the highest improvement in jump height (23.7%) (p<O.Ol) and power (13.8%), whereas force was improved the most by box training (34.9%) from pre-test. By DJ test, the highest improvement in jump height and power was brought by box drills training (27.9% and 19.6% respectively). Force improved 18.8% under the influence of jumps training. There were no significant differences in the EMG peak amplitude and mean power frequency at muscle gluteus maximus, biceps femoris, rectus femoris, vastus medialis, medial gastrocnemius, and tibialis anterior in all types of jumping exercises. Muscle activation patterns differed in eccentric and concentric phases of the testing jumps. Suggested training programmes, can be used as a conditioning programmes for volleyball and basketball players, track and field athletes specialising in vertical and horizontal jumps, they brought in significant improvement in jump characteristics.